Lymphoepithelial Carcinoma Originated from the Sinonasal Cavity: Case Report and Literature Review - Hassan Alhazzani; Saleh Alabood; Ahmed Alhussien; Sahar Alsadah; Abdulrahman Alghulikah; Shuaa Asiri; Ibrahim Alarifi (Case Reports in Otolaryngology)
Background. Sinonasal lymphoepithelial carcinoma (SNLEC) is a rare neoplasm, representing less than 1% of all types of carcinomas and approximately 3% of head and neck tumors. It can affect the nasopharynx due to the rich lymphoid tissue present in this region. Clinical SNLEC presentation varies, ranging from asymptomatic to nonspecific sinonasal symptoms. We report a case of SNLEC and review the literature for SNLEC presentation, diagnosis, management options, and outcomes. Case Presentation. A 38-year-old male, medically free, presented to the emergency department complaining of nasal obstruction, right facial numbness, persistent right-sided headache, intermittent orbital pain, and a history of on/off epistaxis. Imaging showed a destructive mass in the right sphenoid sinus extending to different sinuses and infratemporal fossa. Biopsy confirmed the diagnosis of SNLEC, with immunohistochemistry being positive for Epstein–Barr virus (EBV) and CK8/18. Induction chemotherapy was started with three cycles of cisplatin and gemcitabine, followed by concurrent chemoradiation therapy. Conclusion. SNLEC is rare, with limited reported cases from around the world. It is mostly seen in adults between their fifth and seventh decades with male predominance. SNLEC is diagnosed using imaging, immunohistochemistry, and EBV testing given its strong association with EBV. Owing to the limited cases, there is no standard approach to treating SNLEC. However, most cases managed with radiation and with and without other modalities showed an excellent response in terms of tumor nonrecurrence.